Effect of void fraction models on the film thickness of R134a during downward condensation in a vertical smooth tube - Dalkilic, A. S.; Laohalertdecha, S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In the present study, the void fraction and film thickness of pure R-134a flowing downwards in a vertical condenser tube are indirectly determined using relevant measured data together with an annular flow model and various void fraction models reported in the open literature. The vertical test section is a countercurrent flow double tube heat exchanger with refrigerant flowing down in the inner tube and cooling water flowing upward in the annulus. The inner tube is made from smooth copper tubing of 9.52 mm outer diameter with a length of 0.5 m. The experimental runs are carried out at average saturated condensing temperatures of 40 and 50 degrees C, and mass velocities are around 456 kg m(-2) s(-1), over the vapour quality range 0.82-0.93, while the heat fluxes are between 45.60 and 50.90 kW m(-2). Analysis based on simple void fraction models of the annular flow pattern are presented for forced convection condensation of pure R134a, taking into account the effect of the different saturation temperatures at high mass flux conditions. The comparisons of calculated film thickness show that the void fraction models of Spedding and Chen, and Chisholm and Armand are the most accurate ones with the experimental data due to their low deviation with Whalley's annular flow model over 35 void fraction models presented in this paper. (C) 2008 Published by Elsevier Ltd.
Keywords: Heat transfer; Void fraction; Film thickness; Condensation; Downward flow; R134a; ADIABATIC 2-PHASE FLOW; PRESSURE-DROP; HEAT-TRANSFER; PREDICTION; Thermodynamics; Mechanics